2017
DOI: 10.3389/fnmol.2017.00081
|View full text |Cite
|
Sign up to set email alerts
|

Increased Excitatory Synaptic Transmission of Dentate Granule Neurons in Mice Lacking PSD-95-Interacting Adhesion Molecule Neph2/Kirrel3 during the Early Postnatal Period

Abstract: Copy number variants and point mutations of NEPH2 (also called KIRREL3) gene encoding an immunoglobulin (Ig) superfamily adhesion molecule have been linked to autism spectrum disorders, intellectual disability and neurocognitive delay associated with Jacobsen syndrome, but the physiological roles of Neph2 in the mammalian brain remain largely unknown. Neph2 is highly expressed in the dentate granule (DG) neurons of the hippocampus and is localized in both dendrites and axons. It was recently shown that Neph2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…33,34 It is imaginable that discrepancies are Data from invertebrates and recent data on mammals provide strong support for the notion that Neph2 is involved in spatiotemporal synapse formation, synaptic transmission levels, and synaptic ultrastructure, particularly in the hippocampus. 12,[35][36][37] It is tempting to surmise that Neph2 exerts similar effects on synapses in the auditory, cerebellar and olfactory circuits. Ultrastructural and electrophysiological approaches are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 It is imaginable that discrepancies are Data from invertebrates and recent data on mammals provide strong support for the notion that Neph2 is involved in spatiotemporal synapse formation, synaptic transmission levels, and synaptic ultrastructure, particularly in the hippocampus. 12,[35][36][37] It is tempting to surmise that Neph2 exerts similar effects on synapses in the auditory, cerebellar and olfactory circuits. Ultrastructural and electrophysiological approaches are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type Kirrel3 localizes at or near excitatory synapses (Martin et al, 2015; Roh et al, 2017). Thus, we tested if Kirrel3 missense variants also localize to the cell surface at synapses in neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Most interestingly, the Kirrel3 intracellular domain ends in a conserved PDZ-binding domain, which is a common protein motif of synaptic organizing molecules. It was suggested that mouse Kirrel3 binds to the PDZ domain proteins CASK, PSD95, and ZO-1 (Huber et al, 2003; Gerke et al, 2006; Roh et al, 2017). Other evidence for putative Kirrel3 binding partners comes from studies using Drosophila and C. elegans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations